Penguatan Nilai Moderasi Beragama Dalam Pembelajaran Bahasa Arab Di SMPIT Insan Qur’ani Lampung Tengah - Asep Bambang Susanto; Langgeng Sutopo; Atika Azzahra; Amimah Nur Syamsiyah (STIT Darul Fattah Bandar Lampung, 2023)
The phenomenon of fighting, student brawls, and other juvenile delinquency as well as activities that lead to extremism are challenges that must be overcome. Strengthening the value of religious moderation integrated into learning is the key to creating understanding for students so that harmony and tolerance can be established. The aim of holding this PkM is to strengthen the value of religious moderation in learning Arabic. Stages Implementation methods; 1). conducting interviews with Arabic language subject teachers to find problems. 2). coordinating with the school principal for permission to carry out activities, determining the schedule and participants. 3). Implementation of training activities on strengthening the value of religious moderation in learning. 4). Evaluation of the implementation of the activity by asking questions regarding the value of religious moderation for participants, then opening with a discussion and conclusion session. From the results of the implementation, strengthening the value of religious moderation which is integrated in learning is considered very useful. Among these values ​​are i`tidal, tasamuh, shura, qudwah and others that can be applied in learning.